Effect of Foot Massage on Decreasing Blood Pressure in Hypertension Patients in Bontomarannu Health Center - Fitriani Fitriani; Risnawati H R; Ratnasari Ratnasari; Maria Ulfah Azhar (Journal of Health Science and Prevention, 2019)
Hypertension is called the silent killer because the symptoms are often without complaints. The number of people with hypertension in the world continue to increase every year, estimated that by 2025 there will be 1.5 billion people affected by hypertension. It is also estimated that every year 9.4 million people die from hypertension and complications. when anti-hypertension is needed, non-pharmacological treatment can be used as a complement to get a better treatment effect. One of the non-pharmacological therapies offered to reduce hypertension with massage therapy (massage). The aim of the study was to determine the effect of foot massage on reducing blood pressure in hypertensive patients in the work area of ​​Bontomarannu Health Center, Gowa Regency. This research was conducted on January 2015 using the static group comparison method. The population in this study were residents in the working area of ​​Bontomarannu Health Center and samples were taken with purposive sampling technique with a total sample of 20 people. Based on the results of the study it was found that the administration of foot massage interventions can reduce blood pressure. The statistical test results showed between the systole control group (p-value 0.798), the diastolic control group (p-value 0.726) and the systolic treatment group (p-value 0.004), the diastolic treatment group (p-value 0.005). The administration of foot massage intervention has an influence on the decrease in blood pressure compared to the group that is not given a foot massage intervention.